Cover Feature: Iron Aquo Complex as an Efficient and Selective Homogeneous Photocatalyst for Organic Synthetic Reactions (ChemCatChem 20/2018). Issue 20 (24th October 2018) - Iqbal, Muhammad Faisal; Tominaka, Satoshi; Peng, Wenqin; Takei, Toshiaki; Tsunoji, Nao; Sano, Tsuneji; Ide, Yusuke
Abstract : The Cover Feature shows that iron(III) aquo complexes can be used as a homogeneous photocatalysts for green fine chemical synthesis. In their Communication, M. F. Iqbal et al. demonstrate that the iron aquo complexes catalyze the oxidation of cyclohexane to cyclohexanol and cyclohexanone with a turnover number (TON) of 88 and a nearly 100% selectivity using O2 under irradiation of solar light, whereas existing TiO2 and α‐Fe2 O3 heterogeneous photocatalysts showed low TON and no activity. These results show the potential of such simple iron ions as effective photocatalysts for practical organic synthesis. More information can be found in the Communication by M. F. Iqbal et al. onpage 4509 in Issue 20, 2018 (DOI:10.1002/cctc.201801360 ).